Acute Kidney Injury in Elderly Patients With Chronic Kidney Disease: Do Angiotensin‐Converting Enzyme Inhibitors Carry a Risk?. Issue 6 (14th April 2016) - Chaumont, Martin; Pourcelet, Aline; van Nuffelen, Marc; Racapé, Judith; Leeman, Marc; Hougardy, Jean‐Michel
Abstract : In contrast to angiotensin receptor blockers (ARBs), mainly excreted by the liver, the dosage of angiotensin‐converting enzyme (ACE) inhibitors, cleared by the kidney, must be adapted to account for renal clearance in patients with chronic kidney disease (CKD) to avoid acute kidney injury (AKI). Community‐acquired AKI and the use of ACE inhibitors or ARBs in the emergency department were retrospectively assessed in 324 patients with baseline stage 3 or higher CKD. After stepwise regression analysis, the use of ACE inhibitors (odds ratio [OR], 1.9; 95% confidence interval [CI], 1.1–3.1; P= .02) and the presence of dehydration (OR, 30.8; 95% CI, 3.9–239.1) were associated with AKI. A total of 45% of patients using ACE inhibitors experienced overdosing, which causes most of the excess risk of AKI. These results suggest that dosage adjustment of ACE inhibitors to renal function or substitution of ACE inhibitors with ARBs could reduce the incidence of AKI. Moreover, ACE inhibitors and ARBs should be stopped in cases of dehydration.